PROFIL LSM LASKAR MELAYU BERSATU (LMB) KECAMATAN TENAYAN RAYA MASA BHAKTI 2016-2021 - Sagita, Dedi; Tantoro, Swis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Non-Governmental Organizations become a representative forum that protects, aspires and overshadows the surrounding community, the role of LMB in this research is seen based on the implementation of its work program and the benefits of the implementation of its work program, where if the LMB LSM can implement its work program and the work program implemented has an impact both for the community, especially the Malay tribe in Tenayan Subdistrict, besides this research reveals the purpose, vision and mission, role and profile of the LMB LSM in Tenayan Raya sub-district whether its management is appropriate, how the community responds to this institution and LSM efforts LMB in preserving Malay culture in order to maintain its existence in this Lancang Kuning earth. The profile of the LSM LMB examined this time is located in Tenayan Raya Subdistrict where the area is actually the majority of immigrants or non-Malay ethnic natives in Pekanbaru, the researchers selected 4 informants who will be interviewed, they are members or administrators of LMB LSM Tenayan Raya sub-district . Data retrieval of the research was carried out by interview, observation and documentation. Interviews conducted are structured interviews where the researcher prepares the guidelines for the interview first.Keywords: Profile, Laskar Melayu Bersatu , LSM